A Rare Occurrence of Infantile Hypertrophic Pyloric Stenosis following a Primary Surgical Closure of Gastroschisis in a Neonate - Trassanee Chatmethakul; Jayalakshmi Bhat; Michael Zayek; James G Glasser; Ramachandra Bhat (EL-Med-Pub, 2017)
Please see Fulltext